Retirement scheme : a study of satisfaction towards retirement scheme among the public in Kota Kinabalu city / Dk Nurfatimah Ak Ahmad Shah and Ben-Sakner Neri - Ak Ahmad Shah, Dk Nurfatimah; Neri, Ben-Sakner (2013)
Malaysia was already practice various types of retirement schemes and it is crucial for the public to being satisfied with their retirement scheme chose as they acted as the civil servant, private sector workers, or self-employed. Therefore, this study focuses on determining and knowing whether the public are satisfied with their retirement scheme. A random sample of 104 respondents focusing in Kota Kinabalu City was being studied by gaining their feedbacks regarding their satisfactory of their own retirement scheme. Not surprisingly, the percentage of being satisfied with their retirement scheme and those not satisfied was almost the same by only having slight differences in percentage. Besides, the monthly income and job sector is related to the satisfaction of the respondents on their retirement scheme besides of the need to doing best preparation for retirement age. The flexibility of the retirement scheme should be more suitable to the demand of the public as the findings shows that people more prefer the monthly payment compared to lump sum. The retirement scheme in Malaysia especially in Kota Kinabalu City was still weak in knowledge of the people as the reasons can caused the unsatisfactory among the public which not applicable with their expectations. Hence, the retirement scheme should be suitable for all the job sector in Malaysia as the sectors brought different background of ability to pay and the flexibility features.